DESAIN PEMBELAJARAN KREATIF UNTUK ANAK DALAM SEKOLAH KREATIF RUMAH KREATIF WADAS KELIR - hafidz, Nur; Munastiwi, Erni (Universitas Negeri Jakarta, 2022)
Current learning policies that make schools should create a learning atmosphere that is fun but not stressful. This is a problem to encourage teachers to always be creative in their learning system. Creative teachers are teachers who create creative learning designs for their children. The purpose of creative learning is to create children's creative skills, conditioning and fun activities. This is described in the discussion by answering the question, how to design creative learning for children. The research describes in depth about creative learning designs for children in creative schools at the Wadas Kelir Creative House Creative School. Researchers used descriptive qualitative research methods. Researchers observe objects and find sources of data in the form of creative learning design activities. Creative learning design activities can be drawn as a common thread, namely, (1) creative learning planning, teachers prepare materials, plan activities, and creative media sources; (2) carrying out creative learning, the teacher observes, formulates problems, tries out; create; share; appreciate; (3) assessment and appreciation, the teacher praises the results of understanding, skills, and attitudes of children after creative learning and gives awards to children. As a result, children have the potential for intelligence, creativity, confidence, independence in developing their creativity. This is where children's creativity is built through creative activities that delight children from an early age. So the concept of creative learning design needs to be implemented in every school.